A Four-tier Diagnostic Instrument: An Analysis of Elementary Student Misconceptions in Science Topic - Kartimi Kartimi; Yunita Yunita; Fitri Nurzakiah Fuadi; Istiqomah Addiin (Jurnal Penelitian Pendidikan IPA, 2021)
Learning science in elementary schools encourages students to understand the natural environment more deeply, rationally, and scientifically. However, often the scientific concepts they believe about science topics are not in accordance with the scientific concepts they should be. This misconception is difficult for teachers to diagnose. Special instruments to identify and analyze students' misconceptions are needed. Therefore, this research aims to analyze the misconceptions of elementary school students on the topic of energy using a four-tier diagnostic instrument. The purposed-designed survey method was used in this study. The data were analyzed quantitatively and qualitatively. The participants in this study were 20 fourth grade students in an elementary school in Ciamis Regency. A total of 6 questions in the form of a four-tier diagnostic instrument were used to determine the level of students' conceptions. The results showed that the students have misconceptions about the concept of energy. This can be seen from the average percentage of students' misconceptions of 66.67%. This research is expected to contribute to alternative ways to identify and analyze students' misconceptions using the four-tier diagnostic instrument. In addition, it can be used as a reference for teachers and researchers related to the problem of misconceptions of science in elementary school students